Anti-MRSA Constituents from Ruta chalepensis (Rutaceae) Grown in Iraq, and In Silico Studies on Two of Most Active Compounds, Chalepensin and 6-Hydroxy-rutin 3′,7-Dimethyl ether - Shaymaa Al-Majmaie; Lutfun Nahar; M. Mukhlesur Rahman; Sushmita Nath; Priyanka Saha; Anupam Das Talukdar; George P. Sharples; Satyajit D. Sarker (Molecules, 2021)
Ruta chalepensis L. (Rutaceae), a perennial herb with wild and cultivated habitats, is well known for its traditional uses as an anti-inflammatory, analgesic, antipyretic agent, and in the treatment of rheumatism, nerve diseases, neuralgia, dropsy, convulsions and mental disorders. The antimicrobial activities of the crude extracts from the fruits, leaves, stem and roots of R. chalepensis were initially evaluated against two Gram-positive and two Gram-negative bacterial strains and a strain of the fungus Candida albicans. Phytochemical investigation afforded 19 compounds, including alkaloids, coumarins, flavonoid glycosides, a cinnamic acid derivative and a long-chain alkane. These compounds were tested against a panel of methicillin-resistant Staphylococcus aureus (MRSA) strains, i.e., ATCC 25923, SA-1199B, XU212, MRSA-274819 and EMRSA-15. The MIC values of the active compounds, chalepin (9), chalepensin (10), rutamarin (11), rutin 3′-methyl ether (14), rutin 7,4′-dimethyl ether (15), 6-hydroxy-rutin 3′,7-dimethyl ether (16) and arborinine (18) were in the range of 32–128 µg/mL against the tested MRSA strains. Compounds 10 and 16 were the most active compounds from R. chalepensis, and were active against four out of six tested MRSA strains, and in silico studies were performed on these compounds. The anti-MRSA activity of compound 16 was comparable to that of the positive control norfloxacin (MICs 32 vs 16 μg/mL, respectively) against the MRSA strain XU212, which is a Kuwaiti hospital isolate that possesses the TetK tetracycline efflux pump. This is the first report on the anti-MRSA property of compounds isolated from R. chalepensis and relevant in silico studies on the most active compounds.